Islam for Dummies - Malcolm Clark (--For dummies., 2003)
Whether you live or work alongside Muslims and want to relate to them better, or you simply want to gain a better understanding of the world s second largest religion, Islam For Dummies can help you make sense of this religion and its appeal. From the Quran to Ramadan, this friendly guide introduces you to the origins, practices and beliefs of Islam. Islam For Dummies helps you build bridges of understanding between you and your neighbors in the global village. · Approaching Islam · Tracing the Path of Islamic History · Submitting to God · What Muslims Believe · Standing Before God: Heaven and Hell · The Prophet: Muhammad · The Book: The Qur an · Islamic Tradition and Law · The Five Pillars of Worship: Foundations of Islam · Observing Other Religious Rituals and Customs · Muslim Ethics: Living the Good Life · Shi`ites · Sufis · Exploring Lesser-Known Sects Linked to Islam · Islam in America · Seeking Common Roots: Abrahamic Religion and Beyond · Seeking Common Ground · Meeting the Challenge of Modernity · Ten Muslim Contributions to World Civilization · Ten Islamic Regions in the News Today · Ten Noteworthy Muslims, Past and Present